COMPARISION OF EFFICACY AND SAFETY OF CARBAMAZEPINE AND ESLICARBAZEPINE IN ADULT PARTIAL AND GENERALIZED SEIZURES - Jayasutha.J; Bhargavdilip.S; Kishore.K; Ramasamy.C (Asian Journal of Pharmaceutical and Clinical Research, 2014)
Objective: The objective of this study is to evaluate the efficacy of monotherapy Carbamazepine in comparision with Eslicarbazepine and also to assess adverse drug reactions of Carbamazepine and Eslicarbazepine. Methods: This study was a prospective interventional study.A total of 44 patients were included in the study, of which, 22 patients were under Carbamazepine (Group A) and 22 patients were under Eslicarbazepine (Group B). Results: On comparision with GroupA patients, the seizure frequency was found to be less in Group B with very low incidence of adverse effects. Conclusion: Eslicarbazepine monotherapy was found to be better than carbamazepine in partial and generalized seizure patients. Keywords: Seizures, Carbamazepine, Eslicarbazepine